2008
DOI: 10.1186/1471-213x-8-118
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects in Eya3knockout mice

Abstract: Background: In Drosophila, mutations in the gene eyes absent (eya) lead to severe defects in eye development. The functions of its mammalian orthologs Eya1-4 are only partially understood and no mouse model exists for Eya3. Therefore, we characterized the phenotype of a new Eya3 knockout mouse mutant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 55 publications
(57 reference statements)
1
32
0
Order By: Relevance
“…A previous report describing germline deletion of Eya3 noted no defects in eye development or function, although the mutant mice were smaller than the controls. 27 No examination of vascular development in vivo has been previously reported. Although the present study focused on the role of endothelial EYA3, it is expressed in other relevant cells, including smooth muscle cells and retinal microglia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report describing germline deletion of Eya3 noted no defects in eye development or function, although the mutant mice were smaller than the controls. 27 No examination of vascular development in vivo has been previously reported. Although the present study focused on the role of endothelial EYA3, it is expressed in other relevant cells, including smooth muscle cells and retinal microglia.…”
Section: Discussionmentioning
confidence: 99%
“…The Eya3-deficient mouse was reported to have minor functional deficits, including reduced movement and changes in respiratory, heart, and muscle function. 27 We have previously reported a role for the EYA-PTP activity in endothelial and cancer cell motility. 12,28 Because EC migration is a critical component of angiogenesis, the role of Figure 4 EYA tyrosine phosphatase inhibition suppresses neovascularization in retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Eya1 mutations are associated with isolated cardio-facial syndrome, 12 Eya2 was shown to regulate mTOR, a critical mediator of physiological hypertrophy, 13 and Eya3 mutant mice have been described to have heart problems. 14 …”
mentioning
confidence: 99%
“…13,19 Although a role for Eya1 in cardiac physiology and function to date has not been described, Eya2, Eya3, and Eya4 have been specified to affect cardiac function. 7,13,14 It was recently demonstrated that Eya4 regulation of the Na+/K+-ATPase is crucial for the maintenance of cardiac function in zebrafish; 20 a mouse model of Eya4 deficiency additionally revealed abnormal anatomy in the middle ear cavity and the Eustachian tube, leading to otitis media. 21 However, cardiac abnormalities were not reported in this model.…”
mentioning
confidence: 99%
“…Several other studies also support the role of eya3 as a light-sensing molecule in the retina. For instance, the embryonic zebra fish and mouse retina show eya3 mRNA expression (Soker et al, 2008). Similarly, day-night differences in the eya3 immunoreactivity in the outer nuclear layer support a linkage between the light exposure and eya3 expression in the adult mice retina (Sasaki et al, 2012).…”
Section: Discussionmentioning
confidence: 95%